The Impact of Financial Inclusion and Technology Digitalization on The Development of The Creative Economy in Pamekasan - Tahol, Triana Olivia; Susandini, Aprilina; Hadyarti, Vidi (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine the impact of financial inclusion and technology digitalization on the development of the creative economy in Pamekasan, as measured by indicators of product innovation, marketing innovation, financial system innovation, and human resource management innovation. This study uses a quantitative approach involving 85 respondents as samples. Data was collected through field observations, structured interviews, and questionnaires compiled using a Likert scale. Data analysis was carried out using data instrument tests, classical assumption tests, and hypothesis tests with the help of SPSS 26 software to analyze the data obtained and test the established hypotheses. The results of this study indicate that financial inclusion and technology digitalization partially have a positive and significant effect on the development of the creative economy in Pamekasan. Simultaneously, financial inclusion and technology digitalization significantly affect the development of the creative economy in Pamekasan.